Iodine intake and neonatal thyroid function: A never-ending story - Valentin Varlas; Roxana Georgiana Bors; Roxana Bohiltea; Vlad Dima (Amaltea Medical Publishing House, 2021)
Iodine deficiency in pregnant women can lead to abortion, dysgravidy, intrauterine growth restriction, premature birth, low birth weight, which places the pregnant woman in a group with increased vulnerability to the lack of adequate amounts of iodine. Iodine deficiency in pregnancy can lead to increased perinatal and infant mortality and the prevalence of congenital anomalies. All these aspects shed new light on the many side effects of iodine deficiency during pregnancy. The present paper aligns with the general trend of assessing the maternal-fetal thyroid hormone status and establishing the most accurate indicators for its quantification and taking into account the degree of iodine deficiency and prematurity.